Ethnocentrism in purchasing electronic household appliances in the 21st century: in context of Bangladesh - Rahman, Mohammad Mahamudur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.